Implementing virtual power plant concept in Singapore distribution power grids - Li, Gen. (2014)
This project introduces the characteristics of photovoltaic (PV) panels and storage battery system in the Singapore distribution power system. Their impacts on the power grid are studied as well. The penetration of the PV and storage battery system in a small Singapore HDB distribution power network will be discussed. The effects on the power flow and voltage will be studied based on the comparison between the simulation results obtained before and after the penetration of the PV and storage battery system.